2020
DOI: 10.3389/fphar.2020.00717
|View full text |Cite
|
Sign up to set email alerts
|

miR-378b Regulates Insulin Sensitivity by Targeting Insulin Receptor and p110α in Alcohol-Induced Hepatic Steatosis

Abstract: Insulin resistance has been implicated in alcoholic liver disease. A previous study has shown that microRNAs (miRNAs) play a major role in the production, secretion, and function of insulin. MiRNAs are capable of repressing multiple target genes that in turn negatively regulate various physiological and pathological activities. However, current information on the biological function of miRNAs in insulin resistance is limited. The goal of the present study was to elucidate the role of miR-378b in alcohol-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The specific methods used for cell culture refer to previous protocols [ 23 ]. Moreover, preceding research showed that 200 mM EtOH successfully caused to happen ALD in L-02 cells [ 18 ], so our following experiments were performed with an EtOH concentration of 200 mM.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The specific methods used for cell culture refer to previous protocols [ 23 ]. Moreover, preceding research showed that 200 mM EtOH successfully caused to happen ALD in L-02 cells [ 18 ], so our following experiments were performed with an EtOH concentration of 200 mM.…”
Section: Methodsmentioning
confidence: 99%
“…An miR-378b mimic and inhibitor (including their respective negative controls-NCs) were purchased from GeneChem (Shanghai, China). The plasmid was transferred into cells by electroporation (Bio-Rad Laboratories, Inc., Hercules, CA, USA) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations